Tingkat Pengetahuan Masyarakat terhadap Penggunaan Suplemen Kesehatan pada Masa Pandemi COVID-19 - Indah Septiani Putri; Rita Septiana; Khotimatul Khusna (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
The COVID-19 pandemic caused by SARS-CoV-2 has had a significant impact on public health behavior, including the increasing consumption of health supplements as an effort to strengthen immunity. This study aims to describe the level of knowledge of the people of Gedongan Village RT 01 RW 05 regarding the use of health supplements during the pandemic. Health supplements are defined as products that contain vitamins, minerals, amino acids, and herbal ingredients to support the immune system. The study used a descriptive approach with a survey method, involving 106 respondents who were selected purposively. Primary data was obtained through a structured questionnaire that had been validated, then analyzed descriptively. The results showed that the majority of respondents had a level of knowledge in the sufficient category (54%), followed by the poor category (25%) and the good category (21%). Respondents understood the benefits of supplements as a nutritional supplement, but knowledge related to rules of use, appropriate dosage, and potential side effects was limited. Demographic factors such as age, education, and type of work have an effect on knowledge levels, where respondents of productive age, secondary education, and work with cognitive demands show better understanding. The study concludes the need for continuous health education through health workers, especially pharmacists, with an approach according to demographic characteristics to encourage the use of supplements in a rational, safe, and appropriate manner.